Design of a Stormwater Management System in Lady Irene Campus - Tukashaba, Shafan (East African Nature and Science Organization, 2024)
This project aimed to design an efficient drainage system for Ndejje University's Lady Irene Campus, addressing issues of erosion and flooding exacerbated by recent construction projects. The goal was to create a hydraulic conveyance system that balances environmental protection with structural integrity and affordability. The project involved field reconnaissance, data collection, and analysis of the campus's landscape, soil types, and development trends to inform the design. Methodologically, the project used GPS surveying to create topographical maps and obtained rainfall data to size drainage facilities using the rational method. The peak runoff was calculated considering land use characteristics, while Manning’s formula was applied to design drainage channels and culverts. The design aimed to ensure high hydraulic capacity and prevent erosion with specific slope and material choices. An Environmental Impact Assessment was conducted, addressing noise, dust, water quality, waste management, and ecological impacts. Mitigation measures were recommended to minimize adverse effects during the construction and operation phases. Despite challenges such as limited access to surveying equipment and data, the project concluded with a comprehensive stormwater management plan. Recommendations include rehabilitating the university’s weather station and establishing a project database to support future planning and research. The project underscores the importance of integrating sustainable practices in urban development to safeguard environmental and infrastructural integrity.